The key challenges of multinationals certifying as b corporation: the case of danone - Hazard, Lola Céline (2022)
The B Corporations are a new type of company that commits to putting social and environmental goals at the same level as financial performance. The B Corp certification was initially designed for innovative SMEs which wanted to shape the future of business. To trigger a real shift in our economic system, larger companies need to join the B Corp Movement. Danone is the first multinational that will get fully certified in 2025. By now, they have already certified 50% of their net sales. This case study identifies the key challenges of MNCs joining the B Corp movement. It also highlights the organizational tensions faced by Danone in the journey to certification and how they managed such tensions thanks to the paradoxical approach.